Menanamkan Nilai-Nilai Keorganisasian Bagi Siswa Smkn 4 Kota Bengkulu Dalam Pembangunan Pendidikan - Harius Eko Saputa; Yanuar Rikardo; Evi Lorita; Marida Sariningsih; Yusuarsono Yusuarsono; Muhammad Oky Sumantri; Bimas Endo Purnama (Universitas Dehasen Bengkulu, 2024)
SMK Negeri 4 Bengkulu City on Embedding Organizational Values for Students of SMKN 4 Bengkulu City in Educational Development. The targets of this activity are students of SMK Negeri 4 Bengkulu City who are active in the intra-school student organization (OSIS). The activity method is carried out directly (face-to-face) through exposure to organizational and leadership materials. This PKM activity is carried out in several stages, namely the preparation stage, observation stage, implementation stage, report writing stage, and activity evaluation stage. The results of this activity educate and instill organizational values for students of SMKN 4 Bengkulu City in educational development. This PKM activity is carried out to encourage and motivate students to be more active and foster a sense of belonging, solidarity, caring and develop creativity and innovations in organizations to improve students' soft skills and hard skills. So it is hoped that the achievements achieved by SMK N 4 Bengkulu City students will increase and have a role in the development of Indonesian education.